Pulsed Laser Deposited Nickel Doped Zinc Oxide Thin Films: Structural and Optical Investigations - Tanveer A. Dar; Arpana Agrawal; Pratima Sen (Журнал нано- та електронної фізики)
Structural and optical studies has been done on Nickel doped Zinc Oxide (NixZn1 – xO, x  0.03, 0.05 and 0.07 by weight) thin films prepared by pulsed laser deposition technique. The films are characterized by X-ray diffraction, Uv-vis spectroscopy, X-ray photoelectron spectroscopy. We observed a slight red shift in the optical band gap in the NiZnO subsequent to Ni doping. This shift can be assigned due to the sp-d exchange interaction of Ni- d states with s and p-states of ZnO. Also X-ray photoelectron spectroscopy studies show that Ni has well substituted in + 2 oxidation state by replacing Zn2+.